PENDIDIKAN AGAMA ISLAM MENGAJARKAN NILAI - NILAI HIDUP PADA SISWA DI SEKOLAH SMP N 172 JAKARTA - Nadia Sadila; Ahmad Maulana Pratama; Abel Danka Rahadinata; Abdul Fadhil (Cahaya Ilmu Bangsa Institute, 2024)
This article examines how Islamic religious education teaches life values to students at school. Islamic Religious Education is a planned and systematic effort to guide individuals, especially students, in understanding, appreciating and practicing the teachings of the Islamic religion. The main aim of Islamic religious education is to form a Muslim character who is devout, has noble character, and is able to apply Islamic values in everyday life. Islamic Religious Education has a very important role in shaping the character and life values of students at school. The main role of Islamic religious education in teaching students life values: first, Islamic religious education focuses on developing good morals. students are taught values such as patience, honesty, hard work, and empathy; second, provides a strong moral compass, helping students understand the difference between right and wrong; and third, Islamic religious education teaches a balance between spiritual and material needs.